The impact of Rapid Serial Visual Presentation (RSVP) on reading by nonnative speakers - Boo, Zann; Conklin, Kathy (University of Central Lancashire, 2015)
With the proliferation of cell phones and other small handheld electronic devices, more and more people are using software that presents texts one word at a time. This trend can be attributed to the small screen sizes afforded by these modern electronics. Importantly, software companies often claim that such products, which present texts word-by-word, make reading more efficient, as reading speed is increased without sacrificing comprehension. Alongside this, nonnative speakers are often told to read more in their second language to improve their language skills. This leads to important questions about whether the manner in which reading is done is important. To address this, the current study explores the impact of word-by-word presentation of a text on nonnative reading comprehension, as well as on native speakers who provide a baseline of performance. Nonnative and native speakers were presented with a full text on a piece of paper to read naturally, as well as texts presented one word at a time at rates of 500-wpm and 1000-wpm. For native speakers, reading comprehension was impaired when single words were presented at rates of 500-wpm and 1000-wpm compared to natural reading. When compared to the native speakers, the nonnative speakers show the same pattern of impaired reading comprehension for words presented one at a time at rates of 500-wpm and 1000-wpm compared to natural reading.